Covalent organic framework-based cathodes for beyond lithium-ion batteries - Suleman Suleman; Xiaolong Cheng; Muhua Gu; Yoonseob Kim (Communications Materials)
Abstract Covalent organic frameworks (COFs) are revolutionizing cathode materials for beyond-lithium-ion batteries, leveraging their tunable porosity, modular architecture, and redox-active sites to overcome challenges in the storing alkali metal ions (Na+ and K+) and high-valent metal ions (Zn2+, Ca2+, Al3+, Mg2+, etc.) for electrochemical energy storage. Their unique crystal structure, molecular designability, and storage mechanism enable high specific capacity, low diffusion energy barrier, and structural stability when storing large-radius charge carriers. This review highlights recent advancements in COFs for applications beyond lithium-ion batteries, emphasizing performance optimization methodologies for next-generation cathode materials.